Biological control of the cucurbit powdery mildew pathogen Podosphaera xanthii by means of the epiphytic fungus Pseudozyma aphidis and parasitism as a mode of action - Gafni, Aviva; Calderon, Claudia E.; Harris, Raviv; Buxdorf, Kobi; Dafa-Berger, Avis; Zeilinger-Reichert, Einat; Levy, Maggie (Frontiers in Plant Science, 2015)
Epiphytic yeasts, which colonize plant surfaces, may possess activity that can be harnessed to help plants defend themselves against various pathogens. Due to their unique characteristics, epiphytic yeasts belonging to the genus Pseudozyma hold great potential for use as biocontrol agents. We identified a unique, biologically active isolate of the epiphytic yeast Pseudozyma aphidis that is capable of inhibiting Botrytis cinerea via a dual mode of action, namely induced resistance and antibiosis. Here, we show that strain L12 of P. aphidis can reduce the severity of powdery mildew caused by Podosphaera xanthii on cucumber plants with an efficacy of 75%. Confocal and scanning electron microscopy analyses demonstrated P. aphidis proliferation on infected tissue and its production of long hyphae that parasitize the powdery mildew hyphae and spores as an ectoparasite. We also show that crude extract of P. aphidis metabolites can inhibit P. xanthii spore germination in planta. Our results suggest that in addition to its antibiosis mode of action, P. aphidis may also act as an ectoparasite on P. xanthii. These results indicate that P. aphidis strain L12 has the potential to control powdery mildew.